An empirical analysis of the export-led growth (ELG) hypothesis in the Philippines. - Ballester, Richard; Sinay, Joy (2013)
This article reexamines the relationship between growth and exports of the Philippines for the period 1977–2009 using the methods of Sharma and Panagiotidis [2005] and Feder [1983]. With the shift in the current economic policy toward inclusive growth, it is necessary to assess if indeed the export-led growth (ELG) hypothesis really worked for the country. Specifically, the research investigates the cointegration of exports, imports, and output using the Johansen cointegration test and the Breitung cointegration test; the Granger-causality between exports, investments, and output; and the impact of macroeconomic shocks by employing a vector autoregressive model. In summary, the ELG hypothesis appears to be empirically unsupported for the Philippine case.
Keywords: Economic development -- Mathematical models; Exports